2020
DOI: 10.1038/s41598-020-78472-2
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional in-plane and interfacial thermal transport in graphene/2D-SiC van der Waals heterostructures

Abstract: Graphene based van der Waals heterostructures (vdWHs) have gained substantial interest recently due to their unique electrical and optical characteristics as well as unprecedented opportunities to explore new physics and revolutionary design of nanodevices. However, the heat conduction performance of these vdWHs holds a crucial role in deciding their functional efficiency. In-plane and out-of-plane thermal conduction phenomena in graphene/2D-SiC vdWHs were studied using reverse non-equilibrium molecular dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…The temperature evolution of graphene ( T G ) and 2D-SiC ( T 2D-SiC ) was tracked throughout the entire thermal equilibrium procedure. At each step, the total energy of graphene ( E t ) was also collected in order to calculate the R according to 2 where A R is the graphene/2D-SiC contact area. To reduce data noise, the data points acquired at each time step were averaged after every 100 time steps.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature evolution of graphene ( T G ) and 2D-SiC ( T 2D-SiC ) was tracked throughout the entire thermal equilibrium procedure. At each step, the total energy of graphene ( E t ) was also collected in order to calculate the R according to 2 where A R is the graphene/2D-SiC contact area. To reduce data noise, the data points acquired at each time step were averaged after every 100 time steps.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In this regard, numerous vdWHs have been proposed using graphene and related 2D materials with superior electronic properties, exceptional thermal characteristics, unique mechanical properties as well as other physical properties. In particular, the graphene/2D-SiC vdWH has recently been explored with exotic thermal behavior and unique electronic properties being reported 2 , 28 . In our earlier study, we also reported that graphene/2D-SiC 2 shows exceptional thermal transport across the interface to mitigate the heat dissipation problem in next generation nanoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 2 Due to the rapid shrinking trend of nanoscale devices, structural failure problems have increased considerably and must be solved urgently to realize reliable and efficient NEMS. 3 Since the exfoliation of graphene, 4 , 5 the very first two-dimensional (2D) materials with a honeycomb structure, a new milestone has been achieved to solve the failure problems of NEMS by using the extraordinary mechanical strength of graphene. 6 , 7 However, the zero electronic band gap of graphene 5 is a major limitation in all of these prospects and triggered the scientists to invent other monolayer systems with comparable behavior like graphene.…”
Section: Introductionmentioning
confidence: 99%
“…To develop nanoscale energy harvesting devices, two-dimensional (2D) materials 26 30 are fascinating and promising due to their extraordinary features such as high electron mobility, large quantum spin hall effects, high carrier mobility, and very low thickness. In particular, transition metal dichalcogenides 31 and Janus monolayer material WS-X (X = Se and Te) 32 can demonstrate vertical and in-plane piezoelectrical properties.…”
Section: Introductionmentioning
confidence: 99%